The neurobiology of collective action - Zak, Paul J.; Barraza, Jorge A. (Frontiers in Neuroscience, 2013)
This essay introduces a neurologically-informed mathematical model of collective action that reveals the role for empathy and distress in motivating costly helping behaviors. We report three direct tests of model with a key focus on the neuropeptide oxytocin as well as a variety of indirect tests. These studies, from our lab and other researchers, show support for the model. Our findings indicate that empathic concern, via the brain's release of oxytocin, is a trigger for collective action. We discuss the implications from this model for our understanding why human beings engage in costly collective action.